The impact of vehicular pollution on soil health in the forest ecosystem of Sonamarg Kashmir Himalayas - Tariq A. Bhat; Shafat A. Mir; Manzoor R. Khan; Javeed I. A. Bhat; Ishrat Bashir; Bilal A. Beigh; Humayun Azad (Discover Environment)
Abstract This study was taken to evaluate the influence of vehicular pollution on the accumulation of heavy metals and its impact on soil enzymatic activity along the roadside of the Sonamarg forest ecosystem. Soil samples were obtained from three different sites viz., Sonamarg, Baltal, and Thajwas, each comprises of disturbed area (10 mts.) close to roadside and undisturbed area (150 mts.) away from roadside in two seasons (spring and autumn). Soil heavy metal concentration significantly decreased with distance from the roadside. The decrease in the activities of dehydrogenase and urease and soil organic carbon were found in the disturbed area as compared to undisturbed areas. The concentration of zinc (Zn2+) was found to be maximum, followed by nickel (Ni2+), lead (Pb2+), copper (Cu2+), and cadmium (Cd2+) at all the sampling sites. Significant positive correlations were shown by pH with Pb (r = 0.782**), Zn (r = 0.805**), Cu (r = 0.773**), Cd (r = 0.672**) and negative correlations with dehydrogenase activity (r = −0.795**), urease activity (r = −0.825**) and organic carbon (r = −0.764**). Similarly Pb, showed negative correlation with dehydrogenase activity (r = −0.671**,), urease activity (r = −0.673**) and organic carbon (r = −0.860**). A negative correlation was found between Zn and organic carbon (r = −0.821**) as well as between Cu, urease activity (r = −0.632**) and organic carbon (r = −0.757**). The results indicate that vehicular pollution affects the soil quality due to heavy metal contamination in the fragile Sonamarg forest ecosystem.